2018
DOI: 10.1186/s13018-018-0804-3
|View full text |Cite
|
Sign up to set email alerts
|

An anthropometric study of distal tibiofibular syndesmosis (DTS) in a Chinese population

Abstract: BackgroundTo improve the diagnostic accuracy of distal tibiofibular syndesmoses (DTS), this study quantified the range in variations of the normal DTS in a Chinese population, based on CT scan images.MethodsThe study population comprised 92 patients with unilateral ankle injury. CT scans included the non-injured contralateral DTS. The position of the fibula relative to the fibular notch (incisure) of the tibia was quantified by inclusion or separation indices, based on whether the fibula was within or outside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Furthermore, similar to previous studies, 1,3,6,30 the amount of distal tibiofibular translation after sequential ligament transection varied greatly between specimens. 1,3,7,32 Future cadaveric studies may benefit from matched pairs to serve as an internal control given that recent studies about distal tibiofibular morphology in vivo highlight interpatient differences, 11,29,35 but that the contralateral side in a given patient serves as an effective comparison. These types of studies are arguably better done with noninvasive diagnostic modalities, such as ultrasound, given that few would venture to arthroscopically examine the contralateral normal ankle to establish a baseline value.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, similar to previous studies, 1,3,6,30 the amount of distal tibiofibular translation after sequential ligament transection varied greatly between specimens. 1,3,7,32 Future cadaveric studies may benefit from matched pairs to serve as an internal control given that recent studies about distal tibiofibular morphology in vivo highlight interpatient differences, 11,29,35 but that the contralateral side in a given patient serves as an effective comparison. These types of studies are arguably better done with noninvasive diagnostic modalities, such as ultrasound, given that few would venture to arthroscopically examine the contralateral normal ankle to establish a baseline value.…”
Section: Discussionmentioning
confidence: 99%
“…There are several limitations in our study. (1) We chose to measure FN related parameters at ten mm above tibial plafond, which is consistent with previous studies and easy to compare similar studies, but there were studies that suggested the best measurement site was ve mm above [16,33]. Therefore, certain parameters at different levels could be added in the later study [11].…”
Section: Discussionmentioning
confidence: 79%
“…(1) We chose to measure FN related parameters at 10 mm above tibial plafond, which is consistent with previous studies and convenient to compare with similar studies. But some studies also believed that the best measurement site was 5 mm above 16,31 . Therefore, certain parameters at different levels could be added in the later study 10 .…”
Section: Discussionmentioning
confidence: 99%